Structures of Platinum Oxide Clusters in the Gas Phase - Kerpal, C; Harding, D; Hermes, A; Meijer, G; Mackenzie, S; Fielicke, A (American Chemical Society, 2012)
The structures of small gas-phase PtnO2m+ (n = 1–6, m = 1, 2) cluster cations have been investigated in a combined infrared multiple photon dissociation (IRMPD) spectroscopy and density functional theory (DFT) study. On the basis of the infrared spectra obtained, it is concluded that in most clusters oxygen is bound dissociatively, preferring 2-fold bridge binding motifs, sometimes combined with singly coordinated terminal binding. Comparison of the oxide cluster structures with those of bare cationic platinum clusters reported previously reveals major structural changes induced in the platinum core upon oxygen binding. For some cluster sizes the presence of the Ar messenger atom(s) is found to induce a significant change in the observed cluster structure.